III International Scientific and Practical Conference «Harmonization of approaches to pharmaceutical development», Held on November 25, 2020 - Article Editorial (Разработка и регистрация лекарственных средств)
This material is a collection of the main and most interesting reports made at the NPK "Harmonization of approaches to pharmaceutical development" of the Peoples' Friendship University of Russia. The pharmaceutical industry in the context of globalization of the world economy is constantly changing under the influence of stormy geopolitical processes. This is especially noticeable in the current pandemic environment. The scale of the sales markets for the products of the industry is constantly increasing, which naturally leads to the demand for quick and clear solutions at all stages of pharmaceutical development. In turn, adherence to the requirements of good practices ensures the safety of the finished products of the industry, which is extremely important for humanity. Separately, this applies to the stage of preclinical and clinical trials of drugs, since their conduct is associated with the provision of a number of strict ethical standards. Due to the constant and well-deserved growth in the popularity of medicinal objects of plant origin, the issues of phytochemistry and plant metabolism in relation to the process of pharmaceutical development are also extremely important. In the reports offered to the reader's attention, the entire spectrum of the above issues is considered. The authors offer their own vision of the existing subject problems. Discussion of the proposed issues will undoubtedly arouse the interest of a fairly wide target audience.